Agronomy for Sustainable Sugarcane Production in sub-tropics - Srivastava, T K; Verma, Ram Ratan (Indian Farming, 2017)
Sugarcane still finds favour of growers and may be effectively adopted as a medium to raise farmers’ income and bring about rural prosperity by effective adoption of good agronomic practices. Climatic limitations like adverse temperature during summer and winter months leading to a comparatively short elongation phase, poor adoption of sustainable cultivation practices like residue recycling, balanced nutrient application, soil health management, water efficient irrigation methods, drainage of excess water, scheduling of cane harvest and bio-intensive integrated insect-pest and disease management are responsible for low sugarcane productivity in the subtropics. Further, the climate change induced occurrence of extreme weather events like increasing number of days with higher than normal maximum temperature during summers, erratic rainfall, rising minimum temperature level and extreme cold during ripening phase often come in the way of realisation of high cane productivity in the region.